ANALISIS RELASI PARAMETER PEMOTONGAN BAJA St 43 PADA MESIN BUBUT GDW LZ 350 - Selleng, Kristian (MEKTEK, 2010)
The aim of this research is to find out the correlations among cutting parameters, namely depth of cutting t(mm), cutting speed v (mm/min) and feeding s (mm/rev) of a steel St 43 on. Type of the lathe is GDW LZ 350.This research used experiment method.Data analysis results the below equation: t = (2,483 âˆ’ 0,3936 ln V + 5,44 V âˆ’ 0,863 V ln V ) e S